Evaluation of Performance by Operating Process Improvement Modeling on a Company with Pump Manufacturing - İNAN, AHMET TALAT (My University, 2019)
There may be more than one element affecting quality and efficiency in the manufacturing organizations. As a result of multiple elementsoccurring at the same time, permanent losses occur in final production and quality. Both the customer sense of trust and their satisfactionare negatively affected because of those problems.Failure to achieve targeted levels of quality and productivity in the organization reduces customer satisfaction. Quality and productivity inthe organization are affected by inefficiency in resource utilization, bottlenecks in the production and inefficient workflow design withinthe organization.This study aims to improve production process in a manufacturer of air operated diaphragm pumps by simulation analysis. Most efficientway of utilizing raw materials, manpower, vehicles and equipment is sought by simulation based process improvement. Discrete-event simulationsoftware (Arena) is used to detect problems in the production process such as: transportation, blockage and/or layout. Simulation isused to experiment with process improvement approaches without making changes in the real-world production system.Simulation models of the current state and the proposed future state with improvements to the layout of the production system are created.The results from the models were compared with each other and evaluations were made. The future state simulation model utilizes existingresources for process improvement, without the requirement for additional resource acquisition. Comparison of current state model and futurestate model simulation output data, suggests a 67% increase in the number of products produced per month. It is foreseen that this increasecan greatly affect the operational efficiency and future managerial decisions, and suggestions are made for future works.

İmalat organizasyonlarında kaliteyi ve verimliliği etkileyen birden fazla unsur olabilir. Aynı anda meydana gelen çoklu elemanların bir sonucu olarak, nihai üretim ve kalitede kalıcı kayıplar meydana gelir. Bu sorunlar nedeniyle hem müşteri güven duygusu hem de memnuniyeti olumsuz yönde etkilenmektedir. Kuruluşta hedeflenen kalite ve verimlilik seviyelerinin sağlanamaması müşteri memnuniyetini azaltır. Kurumdaki kalite ve verimlilik, kaynak kullanımındaki yetersizlik, üretimdeki darboğazlar ve organizasyon içindeki yetersiz iş akışı tasarımından etkilenir. Bu çalışma, simülasyonlu analizle hava ile çalışan bir diyafram pompa üreticisindeki üretim sürecini iyileştirmeyi amaçlamaktadır. Simülasyona dayalı süreç iyileştirme ile hammadde, insan gücü, araç ve gereç kullanmanın en etkili yolu aranmaktadır. Kesikli olay simülasyon yazılımı (Arena), üretim sürecindeki sorunları tespit etmek için kullanılır: ulaşım, tıkanma ve / veya düzen. Simülasyon, gerçek dünya üretim sisteminde değişiklik yapmadan süreç iyileştirme yaklaşımlarını denemek için kullanılır. Üretim sisteminin düzeninde iyileştirmelerle mevcut durumun ve önerilen gelecek durumun simülasyon modelleri oluşturulmuştur. Modellerin sonuçları birbirleriyle karşılaştırıldı ve değerlendirmeler yapıldı. Gelecekteki durum simülasyon modeli, ek kaynak edinme şartı olmadan, süreç iyileştirme için mevcut kaynakları kullanır. Mevcut durum modeli ve gelecekteki durum modeli simülasyonu çıktı verilerinin karşılaştırılması, ayda üretilen ürün sayısında % 67 artış olduğunu göstermektedir. Bu artışın operasyonel verimliliği ve gelecekteki yönetim kararlarını büyük ölçüde etkileyebileceği ve gelecekteki çalışmalar için önerilerde bulunacağı öngörülmektedir.
Pompa İmalatı Yapan Bir Firmada Süreç İyileştirme Modellemesiyle İşletmenin Performansının Değerlendirilmesi
Keywords: Kimya, Uygulamalı; Kimya, Tıbbi; Kimya, Organik; Çevre Bilimleri; Matematik; Fizik, Matematik; Mühendislik, Kimya; Mühendislik, Elektrik ve Elektronik; Endüstri Mühendisliği; Mühendislik, Makine; Malzeme Bilimleri, Biyomalzemeler